2020
DOI: 10.5468/ogs.20020
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-6 (IL-6) in predicting gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM) is the most common pregnancy-associated metabolic disorder that is steadily increasing worldwide. Early diagnosis of pregnant women susceptible to GDM is the first step for deploying effective preventive treatment to reduce maternal, fetal, and neonatal complications. The diagnostic process of GDM is still controversial and interleukin-6 (IL-6) is one of the most recent markers used for the diagnosis of GDM. In this study, we aimed to systematically review the role of IL-6 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
1
23
1
2
Order By: Relevance
“…Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were observed in the report of the study. PRISMA contains 27 items related to the content of a systematic and meta-analysis, and includes abstracts, methods, results, discussions, and financial resources [ 13 , 14 , 15 ]. This study was approved by ethnical code IR.ABZUMS.REC.1399.140.…”
Section: Methodsmentioning
confidence: 99%
“…Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were observed in the report of the study. PRISMA contains 27 items related to the content of a systematic and meta-analysis, and includes abstracts, methods, results, discussions, and financial resources [ 13 , 14 , 15 ]. This study was approved by ethnical code IR.ABZUMS.REC.1399.140.…”
Section: Methodsmentioning
confidence: 99%
“…Driven by the discordance in results, a recent systematic review by Amirian et al [ 155 ] has explored the relationship between Il-6 and GDM in studies published between 2009 and 2020 and included 24 articles. The study highlighted the diversity of ethnicities involved, the different measurement methods, but also the numerous criteria used to diagnose GDM (14 different diagnostic criteria) in the studies selected, making significant research synthesis difficult.…”
Section: Cytokinesmentioning
confidence: 99%
“…Placenta-derived inflammatory cytokines can stimulate immune cells and aggravate the immune/inflammatory response, thereby exacerbating chronic inflammation, increasing maternal IR, and inducing β cell failure during pregnancy. [42][43][44][45][46][47][48][49][50] Moreover, the immune cells and inflammatory cytokines are important parts of the placental microenvironment, which is essential for normal pregnancy. [51][52][53] The imbalanced immune infiltration in the placenta participates in the pathogenesis and development of pregnancy-specific diseases, including GDM, and may affect GDM-related adverse pregnancy outcomes and clinical prognosis.…”
Section: Inflammatory Responsementioning
confidence: 99%